The lure of the local senses of place in a multicentered society - Lippard, Lucy R. (New York New Press, 1997)
"In The Lure of the Local, Lucy R. Lippard, one of America's most influential art writers, weaves together cultural studies, history, geography, and contemporary art to provide a fascinating exploration of our multiple senses of place. Expanding her reach far beyond the confines of the art wolrd, she discusses community, land use, perceptions of nature, how we produce the landscape, and how the landscape affects our lives. She consistently makes unexpected connections between contemporary art and its political, social, and cultural contexts." -- Provided by publisher
Includes bibliographical references (pages [293]-320) and index.
Keywords: Human geography -- United States; Geographical perception -- United States; Multiculturalism -- United States; United States -- Social life and customs